PERANAN LSM DALAM PEMBERDAYAAN MASYARAKAT (Studi Atas Perubahan Paradigmatis Gerakan LSM di Indonesia) - Zuhri Humaidi (Politeknik Kesejahteraan Sosial, 2009)
This paper discusses the significance of NGOs in the context of improving social welfare in Indonesia. NGOs are civil society elements that grow in the 1970s, after the government fornm- lated the concept of developmentalism as an ideology of development. In this phase up strategic alliances with the state concerning the development of social welfare and success of the project. In the era of the 1990s, the NGO movement emerged with a strategy that is more opposition to the 1998 reform. While the post-reform effort came back redistribute role of NGOs in the social context has changed. Political openness encourages NGOs to build up new alliances with government and political parties, although this time with a field larger movement. The role of NGOs is not only at the level of empowerment and improvement of social welfare, but as elements that contribute to the creation of Good Governance. This paper concludes that the various shades of transformation that happened, NGOs remain an important element of government as partners in the social wel- fare community.Keywords :. Developmentalism, Good Governance, Civil Society and Paradigm.